Testing the EKC Hypothesis in terms of Trade Openness, Industrial and Construction Development: Evidences from Northern European and Latin American Countries - Kayabas, Yunus Emre (International Journal of Energy Economics and Policy, 2022)
The main research objective is to examine the long-run relationship between trade openness, industrial & construction development, economic growth, energy consumption, and ecological footprint by performing the Westerlund co-integration, FMOLS, DOLS, and CCR tests for Northern European (Denmark, Finland, Netherlands, Norway, and Sweden) and Latin American Countries (Argentina, Brazil, Chile, Colombia, and Uruguay) from 1980 to 2018. Considering the FMOLS, DOLS, and CCR test results of Northern European countries the EKC hypothesis is not confirmed for Finland, Norway and Sweden except Denmark and Netherlands. There is a long-run relationship among industrial & construction development, economic growth, and ecological footprint for both Denmark and Netherlands which verifies the EKC hypothesis from 1980 to 2018. When the remaining countries are examined, the results are opposite. There is no long-run relationship among relevant variables for Finland, Denmark, and Sweden from 1980 to 2018. Besides, there is no effect of industrial & construction development, economic growth, energy consumption, and trade openness on ecological footprint for Finland, Denmark, and Sweden from 1980 to 2018. The EKC hypothesis is not confirmed for Latin American countries as well. Similar results are obtained by using the same variables and other models including FMOLS, DOLS, and CCR for all Latin American countries. The pollution problem in question is of particular concern to developed countries. Because, these countries are forced to use heavy industry, which is far from the nano-technological industry structure and has high environmental degradation. In this context, Denmark should build an artificial island as a precaution against the climate crisis. Another main recommendation is Dutch government should build hydrogen heated homes in order to wage a fight against air pollution.